A Comparative Analysis on Learning Preferences of Students at Faculty of Computer & Mathematical Sciences (FSKM) and Faculty of Business Management (FPP) at Universiti Teknologi Mara (UiTM) / Faiz Zulkifli...[et al.] - Zulkifli, Faiz; Fadhlullah, Afifah; Abu Bakar, Norida; Jahya, Arnida; Ismail, Norfuziana; Hashim, Hadzli; Ahmad Ridzuan, Ahmad Nur Azam (2014)
The purpose of this study is to analyze learning preferences of students from two different faculties at Universiti Teknologi MARA (UiTM), Perak and Melaka Campus. These faculties are Computer & Mathematical Sciences (FSKM) and Business Management (FPP) representing science technology and social sciences respectively. 73 FSKM students and 101 FPP students were involved in this survey project which employed Dunn and Dunn’s Model. The survey form is subdivided into five main elements with 21 sub-parameters representing environmental, emotional, sociological, physiological and psychological. The surveys were conducted online during the last week of lecture for semester April 2014. Descriptive statistics via frequency were performed using bar-chart to describe the data collected. Meanwhile, cross-tabs analyses using the Statistical Package for Social Sciences (SPSS) were conducted to test differences on learning preferences from these two faculties. The objective of the survey is to see how much differences students from these two faculties in choosing their learning preferences with regards to the distinctive background of the two disciplines. From the analyses, several teaching strategies are proposed that can be implemented by lecturers from both faculties.